The influence of democratic leader shipstyle, work environment and extrinsic motivation on affective commitmentin employees of the transportation department of the government Yogyakarta special region - Maria Yosmini Mona; Prayekti Prayekti; Tri Ratna Purnamarini (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to determine the influence of Democratic Leadership Style, Work Environment and Extrinsic Motivation on Affective Commitment in Employees of the Yogyakarta Special Region Government Transportation Office. The type of research used is quantitative research. The population in this study is all employees of the Yogyakarta Special Region Government Transportation Office totaling 53 respondents. Data collection techniques with questionnaire dissemination methods. Data analysis was performed by validity test, reliability test, classical assumption test and multiple linear regression analysis. The results of data analysis with a significant 0.05 show that democratic leadership style has a positive and significant effect on affective commitment, work environment has a positive and significant effect on affective commitment, extrinsic motivation has a positive and significant effect on affective commitment and democratic leadership style, work environment and extrinsic motivation simultaneously affect affective commitment.